Heme Polymerization Inhibition by Tithonia diversifolia (Hemsley) A.Gray Leaves Fractions as Antiplasmodial Agent and Its Cytotoxicity on Vero Cells - Rul Afiyah Syarif; Mustofa Mustofa; Ngatidjan Ngatidjan; Mae Sri Hartati Wahyuningsih (Faculty of Pharmacy, Universitas Gadjah Mada, 2018)
Previous research revealed that the extracts and fractions of Tithonia diversifolia (Hemsley) A.Gray leaves had antiplasmodial activity in vitro. For further development as an antiplasmodial agent, the mechanisms of action and safety of compounds are important to disclose. Heme polymerization inhibition is one of the main targets of antiplasmodial action. The aim of the study was to investigate the activity of T. diversifolia fractions in inhibiting heme polymerization and its cytotoxic effect on Vero cells. Heme polymerization inhibition assay from Bassilico and cytotoxic test on Vero cell using MTT method were conducted for three fractions (F5, F6, and F7) of T. diversifolia leaves. The inhibitory activity of heme polymerization expressed as IC50 and cytotoxicity effect expressed as CC50 were determined by probit analysis. The best heme polymerization inhibition activity was F5 with IC50 = 162.20 ± 57.81 μg/mL followed by F6 and F7 with IC50 216.30 ± 26.56 and 231.54 ± 44.26 μg/mL respectively. All the fractions had a low cytotoxic effect with CC50 for F5, F6, and F7 were over than 100, 34.81 ± 9.94 and 56.26 ± 6.73 μg/mL, respectively and the toxicity index fraction is below 10 or categorized as low selectivity. Conclusion: The fraction of T. diversifolia inhibited heme polymerization in vitro and had low cytotoxic effect on Vero cells but no selective toxicity. Further research using pure compounds may improve its selectivity.